(untitled) (Phenomenology, Humanities and Sciences, 2024)
It is with great pleasure that I undertake this project. I gain pleasure not only from per forming a labor of love for a dear friend, Denis Guénoun, but also to provide a gift for all for all Anglophones. Not since Sartre has such an original voice emerged upon the French scene. Guénoun writes with authority across many disciplines in the grand tradition of French in tellectuals: philosophy, theatre, history, literature, theology; yet he writes with the irreverent and powerful voice necessary to command attention from experts in every one of these fields.